Estimation of Hospital Admissions Respiratory Disease Attributed to PM10 Exposure Using the AirQ Model Within the Greater Athens Area - Ntourou, K.; Moustris, K. P.; Giannouli, M.; Nastos, P. T.; Paliatsos, Athanasios G (PERSPECTIVES ON ATMOSPHERIC SCIENCES, 2016)
{The main objective of this work is the assessment of the annual number of hospital admissions for respiratory disease (HARD) due to the exposure to inhalable particulate matter (PM10), within the greater Athens area (GAA), Greece. Towards this aim, the time series of the particulate matter with aerodynamic diameter less than 10 mu m (PM10) recorded in six monitoring stations located in the GAA, for a 13-year period 2001-2013, is used. In this study AirQ2.2.3 software developed by the WHO, was used to evaluate adverse health effects by PM10 in the GAA during the examined period. The results show that, the mean annual HARD cases per 100,000 inhabitants ranged between 20 (suburban location) and 40 (city centre location). Approximately 70 % of the annual HARD cases are due to city centre residents. In all examined locations, a declining trend in the annual number of HARD cases is appeared. Moreover, a strong relation between the annual number of HARD cases and the annual number of days exceeding the European Union daily PM10 threshold value was found.}